KEPEMIMPINAN TECHNOPRENEUR DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA INOVATIF TENAGA KEPENDIDIKAN - Ihsan, Muzhir; Rahmawati, Ima; Soeganda, Bintang Caraka (JURNAL KAJIAN ISLAM MODERN, 2025)
This study aims to analyze the influence of technopreneur leadership and interpersonal communication on the innovative performance of educational personnel at State Islamic Junior High Schools (MTs Negeri) in Bogor City. A quantitative approach using a survey method was employed. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The study population included all educational personnel in MTs Negeri Bogor City, with a sample of 120 respondents. The results revealed that both technopreneur leadership and interpersonal communication had a positive and significant effect on innovative performance. An R-square value of 0.651 indicates that the two independent variables explain 65.1% of the variance in innovative performance. These findings highlight the significance of technology-driven leadership and effective interpersonal communication in fostering a work environment that supports innovation. The results are expected to serve as a foundation for developing policies to enhance the capacity of educational staff in madrasah settings.